Development of a Rapid Focus Reduction Neutralization Test Assay for Measuring SARS‐CoV‐2 Neutralizing Antibodies. (20th November 2020) - Vanderheiden, Abigail; Edara, Venkata Viswanadh; Floyd, Katharine; Kauffman, Robert C.; Mantus, Grace; Anderson, Evan; Rouphael, Nadine; Edupuganti, Sri; Shi, Pei‐Yong; Menachery, Vineet D.; Wrammert, Jens; Suthar, Mehul S.
Abstract: SARS‐CoV‐2 is a recently emerged human coronavirus that has escalated to a pandemic. There are currently no approved vaccines for SARS‐CoV‐2, which causes severe respiratory illness or death. Defining the antibody response to SARS‐CoV‐2 will be essential for understanding disease progression, long‐term immunity, and vaccine efficacy. Here we describe two methods for evaluating the neutralization capacity of SARS‐CoV‐2 antibodies. The basic protocol is a focus reduction neutralization test (FRNT), which involves immunostaining infected cells with a chromogen deposit readout. The alternate protocol is a modification of the FRNT that uses an infectious clone−derived SARS‐CoV‐2 virus expressing a fluorescent reporter. These protocols are adapted for use in a high‐throughput setting, and are compatible with large‐scale vaccine studies or clinical testing. © 2020 Wiley Periodicals LLC Basic Protocol : Focus reduction neutralization test Alternate Protocol : mNeonGreen‐based focus reduction neutralization test (FRNT‐mNG)